Roads and Ruins : the Symbolic Landscape of Fascist Rome. - Baxa, Paul (Toronto Italian studies., 1910)
Drawing on a wide variety of sources, including war diaries, memoirs, paintings, films, and government archives, Roads and Ruins is a richly textured study that offers an original perspective on a well known story.